METHODOLOGICAL STEPS AND BASIC PRINCIPLES THAT ENSURE EFFECTIVE PROBLEM-SOLVING AND PRACTICAL EXERCISE PERFORMANCE FOR YOUNG TEACHERS (European Journal of Interdisciplinary Research and Development, 2025)
This article discusses the main principles and methodological recommendations for teaching future biology teachers effective and simple methods of solving practical exercises and problems.